Immunostimulatory effect of egg yolk phosvitin phosphopeptides produced by high-temperature and mild-pressure pretreatment and enzyme combinations in RAW 264.7 cells via TLR2/MAPK signaling pathway - Ji-Eun Lee; Jae Hoon Lee; Byungrok Min; Kee-Tae Kim; Dong Uk Ahn; Hyun-Dong Paik (Journal of Functional Foods, 2022)
This study investigated the immunostimulatory effect of egg yolk-derived phosvitin phosphopeptides (PPPs) prepared by high-temperature and mild-pressure (HTMP) pretreatment and enzyme combinations in RAW 264.7 macrophages. Treating RAW 264.7 macrophages with PPPs, especially those produced by HTMP pretreatment and trypsin + Multifect 14L combination (HTMP-TM), significantly increased nitric oxide (NO) production. The PPPs increased NO production by inducing the expression of inducible nitric oxide synthase (iNOS) mRNA in RAW 264.7 cells. The mRNA expression and secretion of pro-inflammatory cytokines (tumor necrosis factor (TNF)-α and interleukin (IL)-6) were also enhanced by PPPs. Furthermore, PPPs activated the mitogen-activated protein kinase (MAPK) signaling pathway, and PPPs-induced NO production was suppressed by MAPK inhibitors and anti-Toll-like receptor 2 (TLR2) antibody in RAW 264.7 cells. In conclusion, the immunostimulatory effects of PPPs on RAW 264.7 cells were due to the activation of TLR2-mediated MAPK signaling pathway.